(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
Tourist Information Centers (TICs) play a significant role in enhancing the tourism experience by serving as hubs for information, orientation, and cultural representation. The design of TIC buildings can influence the way tourists perceive a destination, impacting both their satisfaction and the overall tourism economy. This article explores the principles of designing effective and attractive TIC buildings, integrating architectural aesthetics, functionality, and cultural identity to create a positive and lasting impression on visitors. Tourist Information Centers (TICs) play a pivotal role in enhancing visitor experiences and promoting local destinations. This research aims to explore how architectural design elements of TIC buildings contribute to attracting tourists and supporting tourism growth. The study examines the integration of functionality, cultural identity, aesthetic appeal, and sustainable features to create welcoming and engaging spaces that influence tourist perceptions and behavior. A qualitative descriptive methodology was employed, combining literature reviews, case studies, and observational analyses of selected TICs in Asia-Pacific and Western countries, such as the Japan National Tourism Organization TIC in Tokyo, the Melbourne Visitor Information Center, and the Bali Tourist Information Hub. Data were analyzed through content analysis to identify recurring design principles and their impacts on visitor satisfaction and engagement. Findings indicate that accessible locations, technology integration, cultural representation, and eco-friendly features significantly enhance the effectiveness of TICs in providing memorable experiences. The study underscores that TICs designed with adaptive spaces and modern digital solutions not only meet visitor needs but also boost the local economy by encouraging longer stays and higher spending. This research provides valuable insights for architects, tourism planners, and policymakers in developing innovative, culturally authentic, and sustainable TIC designs that align with contemporary tourism demands.